Hardware IP Security and Trust - Mishra, Prabhat; Bhunia, Swarup; Tehranipoor, Mark.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides an overview of current Intellectual Property (IP) based System-on-Chip (SoC) design methodology and highlights how security of IP can be compromised at various stages in the overall SoC design-fabrication-deployment cycle. Readers will gain a comprehensive understanding of the security vulnerabilities of different types of IPs. This book would enable readers to overcome these vulnerabilities through an efficient combination of proactive countermeasures and design-for-security solutions, as well as a wide variety of IP security and trust assessment and validation techniques. This book serves as a single-source of reference for system designers and practitioners for designing secure, reliable and trustworthy SoCs.
Part I. Introduction -- Chapter 1.Security and Trust Vulnerabilities in Third-party IPs -- PArt II.Trust Analysis -- Chapter 2.Security Rule Check -- Chapter 3.Digital Circuit Vulnerabilities to Hardware Trojans -- Chapter 4.Code Coverage Analysis for IP Trust Verification -- Chapter 5.Analyzing Circuit Layout to Probing Attack -- Chapter 6.Testing of Side Channel Leakage of Cryptographic IPs: Metrics and Evaluations -- Part III -- Effective Countermeasures -- Chapter 7.Hardware Hardening Approaches using Camouflaging, Encryption and Obfuscation -- Chapter 8.A Novel Mutating Runtime Architecture for Embedding Multiple Countermeasures Against Passive Side Channel Attacks -- Part IV -- Chapter 9.Validation of IP Security and Trust -- Chapter 10.IP Trust Validation using Proof-carrying Hardware -- Chapter 11. Hardware Trust Verification -- Chapter 12.Verification of Unspecified IP Functionality -- Chapter 13.Verifying Security Properties in Modern SoCs using Instruction-level Abstractions -- Chapter 14. Test Generation for Detection of Malicious Parametric Variations -- Part V. Conclusions -- Chapter 15.The Future of Trustworthy SoC Design.
Keywords: Electronic circuits; Cryptography; Data encryption (Computer science).; Data protection; Electronics; Microprocessors; Computer architecture; Electronic Circuits and Systems; Cryptology; Data and Information Security; Electronics and Microelectronics, Instrumentation; Processor Architectures